The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.22541/au.165881356.61012218/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introduction history and natural selection jointly shape evolution of a signaling trait during biological invasion

Abstract: Introductions of invasive species to new environments often result in rapid rates of trait evolution. While in some cases these evolutionary transitions are adaptive and driven by natural selection, they can also result from non-adaptive processes associated with the invasion history. Here, we examined the role of adaptive and non-adaptive evolutionary processes in the brown anole (Anolis sagrei), a widespread invasive lizard for which genetic data have helped trace the sources of non-native populations. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
(129 reference statements)
0
1
1
Order By: Relevance
“…This contrasts with results from other phenotypic traits in invasive brown anoles (e.g. Baeckens et al, 2023;Bock et al, 2021;Kolbe et al, 2007;Pita-Aquino et al, 2022) which have reported a stronger effect of ancestry and identified several loci with ancestry-specific effects (e.g. Baeckens et al, 2023;Bock et al, 2021).…”
Section: Genetic Mechanisms Of Evolutionary Stasis Of Cold Tolerancecontrasting
confidence: 84%
See 1 more Smart Citation
“…This contrasts with results from other phenotypic traits in invasive brown anoles (e.g. Baeckens et al, 2023;Bock et al, 2021;Kolbe et al, 2007;Pita-Aquino et al, 2022) which have reported a stronger effect of ancestry and identified several loci with ancestry-specific effects (e.g. Baeckens et al, 2023;Bock et al, 2021).…”
Section: Genetic Mechanisms Of Evolutionary Stasis Of Cold Tolerancecontrasting
confidence: 84%
“…Previous studies have highlighted an important contribution of introduction and hybridization history in shaping trait variation across the invasive range of A. sagrei (e.g. Baeckens et al, 2023; Bock et al, 2021; Kolbe et al, 2007; Pita‐Aquino et al, 2022). Thus, prior to investigating the relationship between CT min and climate variables (described below), we sought to incorporate information on genome‐wide ancestry so that population genetic structure can be properly accounted for.…”
Section: Methodsmentioning
confidence: 99%